The Influence of Consumer Behavior and Electronic Word of Mouth (E-Wom) on the Decision to Purchase Pizza Hut Products in Generation Z in Depok City from a Maqosid Syariah Perspective - Mutaufiq, Ali (PT Inovasi Pratama Internasional, 2024)
This research aims to analyze the influence of consumer behavior and electronic-word of mouth (e-WOM) on the decision to purchase Pizza Hut products among Generation Z in Depok City from a Maqosid Syariah perspective. The importance of this research lies in understanding how these two factors influence purchasing decisions in the context of sharia which focuses on prosperity and balance. The background to the problem includes the increasing influence of digital and social media in the consumption behavior of Generation Z, as well as the lack of literature that discusses the influence of consumer behavior and e-WOM specifically in the fast food industry in Indonesia. This phenomenon is increasingly relevant considering that Generation Z is a significant target market. The novelty of this research is the integration of the Maqosid Syariah perspective in the analysis of consumer behavior and e-WOM, which has not been widely discussed in previous research. The method used was quantitative with a questionnaire as the data collection instrument, involving 150 respondents from Generation Z in Depok City. The research results show that consumer behavior and e-WOM simultaneously have a significant effect on purchasing decisions, with a calculated F value of 137.28 which is greater than the F table of 3.06 at a significance level of 0.05. The t test shows that the coefficient value for consumer behavior is 0.482 and e-WOM is 0.567, with a coefficient of determination (R²) of 0.652, indicating that 65.2% of the variability in purchasing decisions is explained by these two factors. So, consumer behavior and e-WOM have a significant influence on purchasing decisions for Pizza Hut products, and it is important for the company to develop an ethical and transparent marketing strategy in accordance with Maqosid Syariah principles.